Synergy of Reflection and Critical Thinking: a Catalyst for Students' Intellectual Growth - Mariia Lionenko; Olena Huzar (Vasyl Stefanyk Precarpathian National University, 2023)
The article is dedicated to exploring the interaction between reflection and critical thinking in the context of developing students' intellectual abilities. Special attention is given to studying the impact of reflective practices on stimulating critical thinking in younger students and their ability to analyze and perceive information critically and objectively. The article analyzes the fundamental aspects of reflective activities, including its role in developing students' consciousness, self-awareness, and internal processing of acquired information. The authors investigate various methods and techniques of reflection that educators can use to activate students' critical thinking. Specifically, the article offers practical case studies of implementing reflective approaches in the educational process. The primary aim of the article is to raise educators' awareness of the significance of the interaction between reflection and critical thinking as key elements in students' intellectual development. The information presented in the article will contribute to the expansion of methodological foundations for promoting reflective processes in teaching and supporting the development of critical thinking among younger students. The research findings can be practically applied in educational institutions and contribute to improving the quality of education.